Critical Analysis of the Use of Conventional Banks as Custodian Banks in Islamic Mutual Fund Transactions - Harahap, Sarah Khairani; Al Islam, Harisma Annisa; Ana, Lewi (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
There is one important component that raises doubts for capital owners who will invest in Islamic mutual funds, namely the use of conventional banks as custodian banks. The purpose of this study is to find out how sharia economic law reviews conventional banks as custodian banks. This study uses a qualitative method with a literature study approach. Data is obtained from interviewing several potential investors, various regulations related to Islamic mutual funds and custodian banks, as well as literature that reviews the principles of muamalah. It was found that conventional banks that become custodian banks must obtain an application from the Financial Services Authority. To ensure the sharia of this business activity, a cleaning process is set up to remove non-halal elements in the form of interest and other non-sharia risks that may come from the activities of related companies. The reluctance to become an investor is caused by the lack of knowledge about the mechanism of Islamic mutual funds for which literacy is needed. However, there are some potential investors who consistently want the bank used is an Islamic bank. Regulations are needed that require the use of Islamic banks as the only custodian bank, but it must be done carefully and gradually according to the readiness of the Islamic bank in question.